Overcoming Therapeutic Resistance of Bone Sarcomas: Overview of the Molecular Mechanisms and Therapeutic Targets for Bone Sarcoma Stem Cells - Tomohiro Fujiwara; Toshifumi Ozaki (Hindawi Limited, 2016)
Bone sarcomas are heterogeneous malignant tumors that exhibit clinical, histological, and molecular heterogeneity. Recent progress in their multimodal treatment has gradually improved patient prognosis; however, drug resistance and distant metastasis remain unresolved clinical problems. Recent investigations have suggested the existence of cancer stem-like cells (CSCs) in bone sarcomas, which represent a subpopulation of tumor cells with high tumor-forming ability. The hallmarks of CSCs include tumor- and metastasis-forming potential and drug resistance, which are responsible for poor prognoses of bone sarcoma patients. Therefore, elucidation of the molecular mechanisms of CSCs and identification of therapeutic targets could contribute to novel treatment strategies for bone sarcomas and improve patient prognosis. This paper provides an overview of the accumulating knowledge on bone sarcoma stem cells and preclinical analyses to overcome their lethal phenotypes, in addition to a discussion of their potential for novel therapeutics for bone sarcomas.